ANALISIS STUDI SYARIAH DI SEKOLAH DAN MADRASAH DALAM PEMBELAJARAN PAI - Huwaida (FITRAH: International Islamic Education Journal, 2021)
The implementation of Sharia Law (Sharia) in Aceh has been going on for some time. Since the implementation of Sharia Law, many violations of Sharia Law have been found in Aceh. The implementation of Sharia Law must also be accompanied by education related to Sharia Law. So far, at the level of formal education, subject that can be categorized as having a connection with the implementation of Sharia Law in Aceh is PAI (Islamic Religious Education) subject. Therefore, this study aims to examine the application of sharia law study in schools and madrasah through PAI learning. An in-depth analysis is applied to various documents related to the 2013 curriculum, especially PAI subject in schools and madrasah at the upper secondary level. The results show that there has been an application of sharia law study through PAI learning in schools and madrasah. Furthermore, based on document evaluations, it is also found that the time allocation for PAI learning in schools is less than the time allocated for PAI learning in madrasah. The time allocation for PAI learning in madrasah is more due to the fact that each PAI component is a separate subject and has its own time allocation.